Food allergy : Knowledge, Attitude and Practices(KAP) among food handlers in school canteen / Noorazlin Ramli...[et al.] - Wan Nawawi, Wan Nazriah; Mohd Kamal, Malina Hanum; Anuar, Jazira (Faculty of Hotel Management and Tourism, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2017)
This study investigated knowledge, attitude, and practice towards food allergy among food handlers in schools. Through self-reported experiences on food handlers’ knowledge, attitude and practice towards food allergy, the food handlers in the school canteen around Dungun area were surveyed. The data obtained from 146 respondents were captured using 36 items of questionnaire in four sections. Results revealed that the food handlers have moderate knowledge on food allergy. Additionally, some of them assumed that food allergy and food poisoning were on the same path. Half of them understood that food allergy was one of the serious health illnesses but were unsure either it is fatal or not. On the other hand, findings indicated that most of the respondents had positive attitude towards food allergy. In addition, some of them were not aware on their responsibility in preparing food at the premise as they assumed people will not get affected. Additionally, the mean of practice reported that food handlers had a good practice towards food allergy as there was fewer cases occurred in their premises before. Thus, efforts to improve coordination between government agencies, private companies, academicians and experts responsible for providing knowledge can be planned meticulously.